The Effect of Shred Injuries for Basketball on Increasing Leg Muscle Power in the Basketball Team of Public High School 3 Malang City - Rizky Setya Wihatama; Widiawati, Prisca; Ramadhan, Muhammad Putra (Indonesian Journal of Sport Management, 2025)
The purpose of this study was to determine the effect of Shred Injuries on leg muscle power in the SMA Negeri 8 Malang City basketball team. The method in this study used an experimental method, with the design “One-group pretest-posttest design”, which is a one-group research design that exists before (pretest) is given treatment and after (postest) is given treatment. The results in the study showed that the pretest female basketball team's leg muscle power test showed an average value of 41.16, while the posttest leg muscle power test results were 43.50. As well as a significant value of 0.014 for pretest and postest, it means that there is an effect of warm-up injury prevention using Shred Injuries on leg muscle power in the women's basketball team. While the results of research on the men's basketball team show that the pretest leg muscle power test shows that the average has a value of 57.00 for the pretest, while the postest leg muscle power test results are 59.66. As well as a significant value of 0.113 for pretest and postest, it means that there is no effect of warm-up injury prevention using Shred Injuries on leg muscle power in the men's basketball team. In this study it was found that there was no effect of Shred Injuries on the explosive power of the leg muscles in the women's basketball team, but there was an effect on the men's basketball team, so this research is a new finding.